Principles of marketing - Kotler, Philip; Armstrong, Gary (Gary M.) (Pearson, 2012)
Learn how to create value and gain loyal customers. Today's marketing challenge is to create vibrant, interactive communities of consumers who make products and brands a part of their daily lives. To help readers understand how to create value and gain loyal customers, Principles of Marketing presents fundamental marketing information in a comprehensive format, organized around an innovative customer-value framework. The fourteenth edition includes coverage on sustainability and a focus on marketing in today's challenging economic climate.